Drivers of the cash paradox - Jacek Pietrucha (Risks, 2021)
An upward trend in the share of cash in GDP has been observed since the beginning of the 21st century and has not yet been fully explained in the literature. In fact, the interest rate is the only variable that has been well researched and well confirmed as a determinant of the cash/GDP ratio. The novelty of this study is primarily considering new determinants of the share of cash in GDP (including in particular monetization and financial development), as well as testing the significance of uncertainty and institutions. The data cover the period 2001-2020 for 82 countries. The most important conclusions include: the share of cash in GDP is primarily dependent on its lagged values (payment habits) and the ultra-loose monetary policy of central banks. However, some other variables also contribute to this process-such as monetization and crises in the real economy.
Keywords: 330; demand for cash; demand for money; uncertainty; interest rate; monetary policy; electronic payments